Azotea Verde a wellness resort and events lounge in San Pablo City, Laguna - Timkang, Clarisse Lorraine D.
With the gentle breeze, a soft singing of the chimes and the soft rustling of leaves fill the air. Looking at the people on the streets as they go about their day makes one sleepy as they have one arm atop the railing of the Azotea. A feature in the Bahay na Bato that allows for relaxation, socializing, and handing down stories and memories of old. The Azotea Verde: a wellness resort and events lounge in San Pablo City, Laguna will serve as a place of relaxation, rejuvenation, learning and making connections. This project will explore the possibility of building a wellness resort in a periurban setting, which cultivates both the wellness of the guest and the tourism of San Pablo City, the City of Seven Lakes, in the province of Laguna. The project will tackle topics on wellness architecture, eco-friendly design, and inclusive architecture, which will allow for an interesting mix of indoor and outdoor spaces. It seeks to be a model of a wellness resort designed in a periurban community where both the wellness of the citizens and the growth of the tourism sector of the community is considered.